BIMBINGAN TEKNIS PENCATATAN DAN PELAPORAN KEUANGAN BENGKEL ZUL KELUARGA JAYA PEMATANGSIANTAR - Liper Siregar; Nelly Ervina; Debi Eka Putri; Sepbeariska Manurung; Christine Loist (Universitas YPPI Rembang, 2024)
The community service activity focuses on the socialization of technical guidance on financial recording and reporting at Bengkel Zul Keluarga Jaya Pematangsiantar. This aims to provide additional understanding to the owners and employees of the workshop as well as strategies to increase sales turnover. The method used is lectures and discussions related to the topic of community service. The stages of the event include an opening and explanation of the technical aspects of financial recording and reporting commonly used by companies. After the activity is completed, further interviews are conducted to evaluate its impact. The results of the interviews show an increase in the understanding of the owners and employees of Bengkel Zul Keluarga Jaya regarding financial recording and reporting techniques by 90%.